Method for creep age forming of aluminum-lithium alloy component with assistance of laser shock and ultrasonic vibration
Through the creep aging forming method assisted by laser shock and ultrasonic vibration, the problem of large rebound of aluminum-lithium alloy is solved, and the rebound rate is reduced, and the alloy strength and R&D and manufacturing efficiency are improved.
Patent Information
- Application Number
- CN202411674579.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the rebound amount of aluminum lithium alloy after creep aging is too large, which affects structural safety and is difficult to effectively reduce.
The aging forming method of laser shock and ultrasonic vibration-assisted creep is adopted, including solid solution treatment, laser shock treatment, deformation treatment and ultrasonic vibration-assisted creep aging heat treatment. The residual compressive stress and ultrasonic vibration acceleration stress relaxation are introduced through laser shock to reduce rebound volume and rebound rate.
Effectively reduce the rebound amount and rebound rate of aluminum-lithium alloys, refine grains, increase nano-precipitation phase density, improve alloy strength, and shorten R&D and manufacturing cycles.
Smart Images

Figure CN119265496A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloy sheet preparation, and in particular to a method for laser impact and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components. Background Art
[0002] Creep aging forming technology refers to a processing method that utilizes the creep and aging strengthening characteristics of metals to integrate a forming-based manufacturing environment and a forming-based heat treatment environment in time and space, so that the metal undergoes slow deformation and aging precipitation strengthening under certain temperature and stress. It is a new sheet metal forming method developed to achieve high-performance and precise forming collaborative manufacturing of large integral wall panel components.
[0003] After creep aging forming, the deformation of the metal will rebound, which will cause the deformation of the aluminum-lithium alloy component to exceed the design range, affecting the structural safety. Therefore, a creep aging forming method that can effectively reduce the springback of aluminum-lithium alloy is urgently needed. Summary of the invention
[0004] The embodiments of this specification provide a method for laser impact and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components to solve the problem that the prior art cannot effectively reduce the springback amount of creep aging forming of aluminum-lithium alloy.
[0005] To solve the above technical problems, the embodiments of this specification are implemented as follows:
[0006] In a first aspect, the method for forming an aluminum-lithium alloy component by laser shock and ultrasonic vibration assisted creep aging forming provided in the embodiments of this specification includes:
[0007] performing a solid solution treatment on the first aluminum-lithium alloy component to obtain a second aluminum-lithium alloy component;
[0008] Performing laser shock treatment on the entire upper surface or lower surface of the second aluminum-lithium alloy component to obtain a third aluminum-lithium alloy component;
[0009] Performing deformation treatment on the third aluminum-lithium alloy component to obtain a fourth aluminum-lithium alloy component;
[0010] When the fourth aluminum-lithium alloy component reaches a preset deformation, performing ultrasonic vibration assisted creep aging heat treatment on the fourth aluminum-lithium alloy component;
[0011] The fourth aluminum-lithium alloy component after heat treatment is cooled to room temperature to obtain a fifth aluminum-lithium alloy component, and the creep aging forming of the fifth aluminum-lithium alloy component is analyzed.
[0012] An embodiment of the present specification realizes the following beneficial effects: the upper surface or the lower surface of the aluminum-lithium alloy component after solution heat treatment is subjected to overall single-sided laser shock treatment, and the component after laser shock treatment is subjected to ultrasonic vibration-assisted creep aging forming, which can effectively reduce the rebound amount and rebound rate of the aluminum-lithium alloy after creep, refine the grains, increase the density of the nano-precipitation phase, improve the alloy strength, and shorten the research and development and manufacturing cycle of the aluminum alloy component. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0014] Figure 1 A schematic flow chart of a method for forming an aluminum-lithium alloy component by laser shock and ultrasonic vibration assisted creep aging forming according to an embodiment of this specification;
[0015] Figure 2 A schematic diagram of the structure of a creep aging device provided in an embodiment of this specification;
[0016] Figure 3a A front view of the overall device for creep aging forming provided in the embodiment of this specification;
[0017] Figure 3b A side view of the overall device for creep aging forming provided in the embodiment of this specification;
[0018] Figure 4 A schematic diagram of the springback of a lithium alloy component provided in an embodiment of this specification;
[0019] Figure 5 A schematic diagram of sample positions for hardness testing provided in the embodiments of this specification;
[0020] Figure 6 A schematic diagram showing the comparison of hardness values of creep-aged alloys after two process treatments provided in the embodiments of this specification;
[0021] Figure 7 Optical microstructure morphology of ultrasonic vibration assisted creep aging alloy without laser shock treatment and after laser shock treatment provided in the embodiments of this specification;
[0022] Figure 8 A statistical schematic diagram of average grain sizes at different positions of ultrasonic vibration assisted creep aging alloys without laser shock treatment and after laser shock treatment provided in the embodiments of this specification;
[0023] Fig. 9 A schematic diagram of the precipitation morphology of the ultrasonic vibration assisted creep aging alloy without laser shock treatment and after laser shock treatment provided in the embodiments of this specification;
[0024] Fig.10 A schematic diagram comparing the springback amount and springback rate under two processes provided in the embodiments of this specification;
[0025] Fig.11 A schematic diagram of an application scenario of the method for laser shock and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components provided in an embodiment of this specification.
[0026] Description of the drawings: 1—locking nut; 2—fastening bolt; 3—punch; 4—die; 5—ventilation hole; 6—high temperature furnace; 7—support platform; 8—ultrasonic generator; 9—ultrasonic transducer; 10—ultrasonic amplitude transformer; 11—connecting bolt; 12—connecting plate; 13—aluminum-lithium alloy component. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of one or more embodiments of this specification clearer, the technical solutions of one or more embodiments of this specification will be clearly and completely described below in combination with the specific embodiments of this specification and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of this specification, not all of the embodiments. Based on the embodiments in this specification, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of one or more embodiments of this specification.
[0028] The technical solutions provided by the embodiments of this specification are described in detail below in conjunction with the accompanying drawings.
[0029] The method of laser shock and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components provided in the embodiment of the specification is specifically described in conjunction with the accompanying drawings.
[0030] Figure 1 A schematic flow chart of a method for laser shock and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components provided in an embodiment of this specification.
[0031] like Figure 1 As shown, the process may include the following steps:
[0032] Step 110: performing a solution treatment on the first aluminum-lithium alloy component to obtain a second aluminum-lithium alloy component.
[0033] In the embodiments of this specification, the aluminum-lithium alloy components are first solution treated, kept at 505°C for 40 minutes, and then quenched in room temperature water. After the solution treatment, they need to be naturally aged at room temperature for 24 hours to allow the aluminum-lithium alloy components to reach a stable state.
[0034] In practical applications, in order to establish the creep aging constitutive model of aluminum-lithium alloy components and accurately predict the springback of components, aluminum-lithium alloy test plates can be used for experimental research. Commercial 3mm thick 2195 aluminum-lithium alloy hot-rolled plates are used. The plate size used for creep aging tests is 80mm×10mm, and the length direction (10mm) is the rolling direction.
[0035] Step 120: Perform laser shock treatment on the entire upper surface or lower surface of the second aluminum-lithium alloy component to obtain a third aluminum-lithium alloy component.
[0036] In the related art, there is a method of performing laser shock assisted creep aging forming on a part of an aluminum alloy component. However, when the aluminum alloy component after local laser shock is subjected to creep, the creep deformation and aging strengthening of the creep aging are uneven, which is not conducive to the establishment of the subsequent creep aging constitutive model.
[0037] In the embodiments of the present specification, one of the surfaces of the aluminum-lithium alloy component after solution treatment is subjected to laser shock treatment as a whole. The single-sided overall laser shock can obtain a uniform initial structure, which is beneficial for establishing a creep aging constitutive model, and further can accurately predict the springback of the alloy component, reduce the number of springback compensation times and mold repair times, greatly shorten the research and development and manufacturing cycle of the aluminum alloy component, and save research and development costs.
[0038] In practical applications, a group of aluminum-lithium alloy components that have not been subjected to laser shock treatment can be set up as a control group.
[0039] Step 130: Perform deformation treatment on the third aluminum-lithium alloy component to obtain a fourth aluminum-lithium alloy component.
[0040] Step 140: When the fourth aluminum-lithium alloy component reaches a preset deformation, the fourth aluminum-lithium alloy component is subjected to an ultrasonic vibration-assisted creep aging heat treatment.
[0041] In the embodiments of the present specification, the lithium alloy component to be formed is placed on a mold with a certain external shape and profile, and mechanical loading or vacuum loading is used to make it fit the external shape and profile of the mold.
[0042] When the lithium alloy component completely fits the outer surface of the mold, the lithium alloy component and the mold are pushed into a heating furnace or autoclave together, and the temperature and pressure are increased according to the pre-set process system, and maintained at a suitable aging temperature and pressure for a period of time. During this process, the lithium alloy component undergoes creep, stress relaxation forming and aging precipitation strengthening.
[0043] While the aluminum-lithium alloy components are being kept warm, creep aging forming with ultrasonic vibration amplitude is performed on the components, and creep aging forming laser shock treated aluminum-lithium alloy components are achieved under the composite energy field of aging temperature and ultrasonic vibration.
[0044] Step 150: Cool the fourth aluminum-lithium alloy component after heat treatment to room temperature to obtain a fifth aluminum-lithium alloy component, and analyze the creep aging forming of the fifth aluminum-lithium alloy component.
[0045] In the embodiment of this specification, after the creep aging is completed, the temperature and pressure on the aluminum-lithium alloy component are unloaded. At this time, due to the constraints of the aging heat treatment system, the creep deformation in the forming stage cannot completely convert the elastic deformation generated in the loading stage into plastic deformation, and the aluminum-lithium alloy component will experience a certain amount of rebound. The rebound amount of the fifth aluminum-lithium alloy component is analyzed and calculated.
[0046] In practical applications, a comparative analysis of creep aging forming of the fifth aluminum-lithium alloy component and the aluminum-lithium alloy component that has not been subjected to laser shock treatment can be performed. Creep aging forming of the component after laser shock treatment can effectively reduce the amount of springback after creep of the aluminum-lithium alloy.
[0047] It should be understood that the order of some steps in the methods described in one or more embodiments of this specification can be interchanged according to actual needs, or some steps can be omitted or deleted.
[0048] In the embodiments of the present specification, the upper or lower surface of the aluminum-lithium alloy component after solution heat treatment is subjected to overall single-sided laser shock treatment, and the component after laser shock treatment is subjected to ultrasonic vibration assisted creep aging forming, which can effectively reduce the rebound amount and rebound rate of the aluminum-lithium alloy after creep, refine the grains, increase the density of the nano-precipitation phase, and improve the alloy strength, thereby shortening the research and development and manufacturing cycle of aluminum alloy components.
[0049] based on Figure 1 The method in this specification also provides some specific implementation plans of the method, which are described below.
[0050] Optionally, before the upper surface or the lower surface of the second aluminum-lithium alloy component is subjected to laser shock treatment as a whole in the embodiments of this specification, the method may further include:
[0051] The working parameters of the laser shock treatment are set according to the thickness of the aluminum-lithium alloy component, and the working parameters at least include shock energy, spot diameter, spot overlap rate, pulse width, and number of shocks.
[0052] In the embodiments of this specification, for thick plates, a larger laser energy can be used, but it should not be too large, otherwise it will cause serious warping of the plate or introduce compressive stress on the back of the laser impact plate surface, which is not conducive to reducing springback; for thin plates, a smaller laser energy is used and multiple impacts are performed. This treatment can not only introduce a larger residual compressive stress on the plate surface, promote stress relaxation and enhance precipitation strengthening, but also refine the grains and improve the alloy strength. The residual compressive stress after laser treatment can be measured by X-ray diffraction testing technology. When the residual compressive stress obtained is large and uniform, the energy at this time is determined as the final laser impact energy.
[0053] In practical applications, for 3mm thick 2195 aluminum-lithium alloy components, the laser shock energy is selected to be a smaller 3J. The spot diameter during the laser shock treatment process is 3mm, the spot overlap rate is 50%, and the pulse width is 10ns. To ensure the effect of the laser shock treatment, the single surface is repeated 3 times.
[0054] Optionally, before the deformation treatment is performed on the third aluminum-lithium alloy component in the embodiment of this specification, the method may further include:
[0055] The third aluminum-lithium alloy component is placed in a creep aging device, wherein the creep aging device at least includes a male mold and a female mold matching the male mold; the upper surface after laser shock treatment or the lower surface after laser shock treatment is in contact with the surface of the male mold, and the other surface is in contact with the surface of the female mold;
[0056] The creep aging device is loaded by using a press machine so as to cause the third aluminum-lithium alloy component located in the creep aging device to deform.
[0057] Figure 2 This is a schematic diagram of the structure of the creep aging device provided in the embodiments of this specification.
[0058] like Figure 2 As shown, the aluminum-lithium alloy component is placed in a creep aging device for deformation treatment, and the surface treated with laser shock is brought into contact with the surface of the punch; the surface not treated with laser shock is brought into contact with the surface of the die, and the surface of the plate in contact with the surface of the punch after bending is subjected to compressive stress, and the surface in contact with the punch after laser shock is subjected to residual compressive stress. The superposition of these two compressive stresses causes the component to undergo greater creep deformation, which can reduce the springback of the creep aging component.
[0059] The neutral plane is the middle layer in the thickness direction of the plate. After the plate is bent, the side above the neutral plane, i.e. the concave side, is subjected to compressive stress, and the side below the neutral plane, i.e. the convex side, is subjected to tensile stress. Residual compressive stress is introduced to one side of the plate through laser shock treatment. This residual compressive stress is superimposed on the bending compressive stress on the concave side after the plate is bent, increasing the total compressive stress on the concave side, thereby driving a greater stress relaxation and accumulating a greater creep deformation under a greater compressive stress, thereby reducing the springback rate of the aging formed component.
[0060] Figure 3a This is a front view of the overall device for creep aging forming provided in an embodiment of this specification.
[0061] Figure 3b A side view of the overall creep aging forming device provided in an embodiment of this specification.
[0062] The aluminum-lithium alloy component is placed in a creep aging device for deformation treatment. The process of deformation treatment of the aluminum-lithium alloy component is the loading stage, such as Figure 3a and Figure 3b As shown, the press machine forms a certain pressure on the punch through the control of the tightening bolts and nuts on the creep aging device, and the aluminum-lithium alloy component sandwiched between the concave and convex dies is pressed and formed. By continuously tightening the nuts in the upper die seat, the aluminum-lithium alloy component is completely fitted with the concave and convex mold surfaces, thereby completing the loading of the aluminum-lithium alloy component.
[0063] The mechanical loading method using concave and convex dies can not only realize the loading and mold-fitting of small-curvature wall panel components, but also easily realize the fitting of large-curvature wall panels with the mold after loading. Compared with air pressure loading, it can form aluminum alloy wall panel components with different curvature sizes and curvature forms (single curvature, double curvature or complex curvature), and the curvature size and curvature form are not restricted.
[0064] Optionally, the ultrasonic vibration assisted creep aging heat treatment of the fourth aluminum-lithium alloy component in the embodiments of this specification may specifically include:
[0065] placing the fourth aluminum-lithium alloy component in a high temperature furnace and heating it to a preset temperature;
[0066] The fourth aluminum-lithium alloy component in the creep aging device in a heat-insulating state is subjected to ultrasonic vibration treatment at a preset vibration frequency.
[0067] In the embodiments of this specification, the process of heat treatment of aluminum-lithium alloy components for ultrasonic vibration-assisted creep aging is the creep aging forming stage. After loading is completed, the die and punch are locked with bolts and nuts, and the entire device is placed in a high-temperature furnace. During this process, the amplitude transformer extends out of the furnace through the air convection holes of the high-temperature furnace, and then the high-temperature furnace switch is turned on, and the entire device is heated to the optimal aging temperature of aluminum-lithium alloy, 180°C, at a heating rate of 2°C / min, and kept warm for 12 hours.
[0068] While the aluminum-lithium alloy components are being kept warm, creep aging forming of the components with ultrasonic vibration amplitude is performed. The ultrasonic transducer and the amplitude transformer are fixed together by threaded connection, and then the power supply of the ultrasonic generator is started to apply ultrasonic vibration. The creep aging forming of the aluminum-lithium alloy components treated with laser shock treatment is realized under the composite energy field of aging temperature and ultrasonic vibration.
[0069] Ultrasonic vibration can accelerate the stress relaxation inside the component and increase the stress relaxation of the component during the entire creep aging forming process, which is conducive to producing a larger creep amount and thus reducing springback.
[0070] Further, optionally, in the embodiment of this specification, if the preset vibration frequency is the natural frequency of the creep aging device, before performing ultrasonic vibration treatment on the fourth aluminum-lithium alloy component in the creep aging device according to the preset vibration frequency, the method may further include:
[0071] The mechanical performance parameters of the creep aging device are obtained and combined with a finite element simulation algorithm to determine the natural frequency of the creep aging device.
[0072] Specifically, according to the three-dimensional structure of the creep aging device and the three-dimensional structure of the aluminum-lithium alloy component located in the creep aging device, three-dimensional models of the creep aging device and the aluminum-lithium alloy component are established respectively, and the creep aging device and the aluminum-lithium alloy component are fully constrained and assembled to obtain a three-dimensional assembly model.
[0073] The three-dimensional assembly model is divided into finite element unit meshes. The finite element unit type is C3D8R, and the unit size is 5mm, which ensures both precise accuracy and computational efficiency.
[0074] Ultrasonic waves with a frequency of 12 kHz to 50 kHz are applied to the three-dimensional assembly model, and the amplitude of ultrasonic vibration is between 1 μm and 100 μm.
[0075] The mechanical property parameters of the creep aging device and the aluminum-lithium alloy components are set, including stress-strain data, elastic modulus, Poisson's ratio and density. The constraint boundary of the entire device consisting of the creep aging device and the aluminum-lithium alloy components is set, and the plane in contact between the device and the high-temperature furnace is fixedly constrained.
[0076] The modal analysis in Abaqus software is used to perform spectrum analysis on the entire device to obtain the natural frequency of the creep aging device. Abaqus is a powerful finite element software for engineering simulation.
[0077] Optionally, the method described in the embodiments of this specification may also include:
[0078] Determining a first curvature radius of the fourth aluminum-lithium alloy component according to the curvature radius of the profile surface of the concave die;
[0079] Using preset reverse engineering software to perform solid modeling to determine a second radius of curvature of the fifth aluminum-lithium alloy component;
[0080] The springback amount and springback rate of the creep aging forming of the aluminum-lithium alloy are determined according to the first radius of curvature and the second radius of curvature.
[0081] Figure 4 A schematic diagram of the springback of a lithium alloy component provided in an embodiment of this specification.
[0082] In the embodiments of this specification, a 3D laser scanner is used to obtain the point cloud of the lithium alloy component after laser impact and ultrasonic vibration assisted creep aging forming, and the point cloud is packaged, and a reverse engineering software (Geomagic DesignX) is used for solid modeling and measurement. Figure 4 As shown, the radius of curvature of the lithium alloy component after rebound is H', and the radius of curvature of the lithium alloy component before rebound is H, where H is the radius of curvature Q of the concave mold surface minus the thickness t of the lithium alloy component, that is, H = Qt. Therefore, the rebound amount ΔH of the lithium alloy component is H-H', and the rebound rate of the lithium alloy component is δ = (H-H') / H.
[0083] Optionally, after the creep aging device after the heat treatment is cooled to room temperature to obtain the fifth aluminum-lithium alloy component in the embodiment of this specification, the method further includes:
[0084] The upper and lower surfaces of the fifth aluminum-lithium alloy component are observed and hardness tested, and the microstructure and hardness changes of the fifth aluminum-lithium alloy component are analyzed.
[0085] Figure 5 A schematic diagram of the sample positions for the hardness test provided in the embodiments of this specification.
[0086] The size of the micro-Vickers hardness can characterize the relationship between the sample microstructure and mechanical properties. The locations of the metallographic samples selected for the micro-Vickers hardness test of the aging alloy with and without laser shock treatment are as follows: Figure 5As shown in Figure 1, 2 and 3, the metallographic specimens were tested for hardness using a HVS-1000A Vickers hardness tester according to the relevant requirements of GB / T 4340.1-2009. The micro-Vickers hardness test conditions were: load 200gf, dwell time 10 seconds, and test spacing 2mm. In addition, the test position of the laser shock treated specimens was on the surface that had undergone laser shock treatment (the side that fits the punch surface), and the test position of the specimens that had not undergone laser shock treatment was also on the side that fits the punch surface. Each position was tested 5 times, and the average value was taken as the final value.
[0087] Figure 6 This is a schematic diagram comparing the hardness values of creep-aged alloys after two process treatments provided in the embodiments of this specification.
[0088] The hardness of metal materials can indirectly reflect the strength of the material. Generally speaking, the higher the hardness value of the material, the better the strength of the material. Figure 6 The hardness value changes of creep-aged alloys at different positions with and without laser shock treatment are shown. It can be clearly seen that the hardness value of the creep-aged alloy after laser treatment is greater than that of the creep-aged alloy without laser shock treatment. In addition, after the two processes, the hardness values of positions 1#, 2# and 3# are not much different. Specifically, the average hardness of the creep-aged alloy after laser shock treatment is about 158HV, while the average hardness of the creep-aged alloy without laser shock treatment is about 129HV. Compared with the creep-aged alloy without laser shock treatment, the hardness value of the creep-aged alloy after laser shock treatment is increased by about 22%. These results show that laser shock treatment of the initial sheet surface before creep aging is beneficial to the improvement of the hardness and strength of the aging alloy. The above experimental results are closely related to the microstructure of the alloy after the two processes. Therefore, it is necessary to conduct an in-depth analysis of the microstructure of the sheet after the two processes.
[0089] In practical applications, in order to test whether there are significant changes in the microstructure morphology and grain size of ultrasonic vibration-assisted creep-aging alloys before and after laser shock treatment, the sample structures after the two processes were characterized by optical microscopy. The samples used for organizational characterization were selected as follows: Figure 5 The size of the 1# position shown is about 5mm×5mm×1.5mm. The thin slice sample was then polished with 500#, 1000# and 3000# water-abrasive sandpaper and mechanically polished with silica suspension to achieve a mirror effect. Finally, it was corroded with Keller reagent (2.5% HNO3+1.0% HF+1.5% HCl+95% H2O) for 10s.
[0090] Figure 7The optical microstructure morphology of the ultrasonic vibration-assisted creep-aging alloy without laser shock treatment and after laser shock treatment provided in the embodiments of this specification. It can be seen that the grains of the creep-aging alloy after the two process treatments are distributed in a gradient from the surface layer to the middle layer (i.e., the neutral layer) of the plate, with small grain size on the surface and larger grain size in the middle layer. Since the initial plate has undergone hot rolling, the surface layer of the plate that has not been treated with laser shock treatment undergoes recrystallization due to large plastic deformation, while the middle layer of the plate has small plastic deformation and small energy storage and no recrystallization occurs, thereby retaining larger grains. Comparing the microstructure of the creep-aging alloy without laser shock treatment ( Figure 7 (a) It can be found that the grain size of the creep-aged alloy is significantly reduced after laser shock treatment, especially in the surface layer of the plate.
[0091] Figure 8 This is a statistical schematic diagram of the average grain size at different positions of the ultrasonic vibration assisted creep aging alloy without laser shock treatment and after laser shock treatment provided in the embodiments of this specification.
[0092] For quantitative analysis, the surface layer to the middle layer was divided into six sections, and the average grain size of different regions was statistically analyzed using Image software, such as Figure 8 As shown in the figure, the grain size of creep-aged alloy after laser shock treatment is lower than that of creep-aged alloy without laser shock treatment in different regions, and the difference in average grain size in the same region under the two process conditions gradually decreases from the surface to the middle layer of the plate. The most obvious difference appears in the surface layer of the plate (region 1), where the maximum average grain size difference ΔD = D0-D L , where D0 and D LThey represent the average grain size of creep-aged alloys before and after laser shock treatment, respectively. ΔD is 49μm. The area with the smallest difference appears in the middle layer of the plate (area 6#), and the minimum average grain size difference in this area is 4μm. The main reason for the difference in the microstructure of creep-aged alloys after the two processes is that after laser shock treatment, larger grains will also be broken into small grains due to laser shock. In addition, the surface of the material undergoes severe plastic deformation due to laser shock. These grains with high strain energy undergo recrystallization during the subsequent creep aging forming process (creep temperature 180℃). The above reasons combined lead to a significant decrease in the grain size of the surface of the material. The middle layer is greatly affected by laser shock, so the average grain size does not change significantly. It is well known that the average grain size is closely related to the strength and hardness of the alloy. Generally speaking, according to the Hall-Petch formula, the smaller the grain size, the higher the strength of the material and the greater the hardness value. The reason why the hardness of creep-aged alloy after laser shock treatment is greater than that of creep-aged alloy without laser shock treatment is partly due to the fine grain strength, especially in the surface area of the plate. In addition, the difference in nano-precipitation behavior during creep aging will also significantly affect the hardness of the alloy, so it is necessary to characterize and analyze the nano-precipitation behavior of the alloy under the two process conditions.
[0093] In order to explore the nano-precipitation behavior of heat-treatable aluminum-lithium alloy under two process conditions, scanning transmission electron microscopy (STEM) was used to observe the nano-precipitation phase inside the alloy after the two process treatments. The samples used for transmission observation were from Figure 5 The sample size was 5 mm × 5 mm × 0.5 mm at the 1# position. The sample preparation process for STEM observation was as follows: First, the sample surface was ground to 50 μm using 2000# water-grinding paper. Subsequently, the sample was double-jet electropolished at about -10°C and 20V electrolyte, resulting in a film with a diameter of about 3 mm.
[0094] Fig. 9 Schematic diagram of precipitation morphology of ultrasonic vibration assisted creep aging alloy before and after laser shock treatment provided in the embodiments of this specification.
[0095] like Fig. 9 As shown, the diffraction spots and morphology of the nano-precipitated phase of the ultrasonic vibration assisted creep aging alloy before and after laser shock treatment are shown. From the selected diffraction spots, it can be found that Fig. 9 (a) and Fig. 9 (b) After the two process treatments, the main precipitated phase is T1 (Al2CuLi) phase, which has a significant strengthening effect. Fig. 9(c) and 9(d) are high-angle annular dark field images (HAADF) of creep-aged alloys without laser shock and after laser shock treatment, respectively. It can be seen that the nano-precipitates inside the alloys after the two processes are T1 phases with two variants. Compared with the distribution and size of the precipitates of creep-aged alloys without laser shock, the precipitates of creep-aged alloys after laser shock are more densely distributed and smaller in size. Small and dense precipitates can more effectively hinder the movement of dislocations. When dislocations encounter precipitates, they must overcome additional resistance to continue moving. The size of this resistance is closely related to the size and number of precipitates. The finer, more numerous and denser the precipitates, the more difficult it is for dislocations to bypass or cut them, which leads to an increase in the strength of the material, and indirectly causes an increase in the hardness of the material.
[0096] Fig.10 A schematic diagram comparing the springback amount and springback rate under the two processes provided in the embodiments of this specification.
[0097] like Fig.10 As shown, compared with the ultrasonic vibration assisted creep aging formed sheet without laser shock treatment, the springback of the ultrasonic vibration assisted creep aging formed sheet after laser shock treatment is effectively reduced, specifically, from 4.5mm without laser shock treatment to 2.8mm after laser shock treatment. The corresponding springback rate dropped from 30% without laser shock treatment to 18.7% after laser shock treatment, a decrease of about 37.8%. It shows that laser shock treatment can significantly reduce the springback of creep aging formed components, which also means that laser shock treatment can improve the creep deformation of the sheet during creep aging, and at the same time, it can also homogenize the distribution of precipitation phases and refine the size of precipitation phases to improve the hardness or strength of the aging alloy.
[0098] Fig.11 A schematic diagram of an application scenario of the method for laser shock and ultrasonic vibration assisted creep aging forming of aluminum-lithium alloy components provided in an embodiment of this specification.
[0099] In practical applications, the sample can be first solution treated with the treatment parameters of 505℃ insulation for 40 minutes, followed by water quenching in room temperature water. After solution treatment, it needs to be naturally aged at room temperature for 24 hours. The experiment was divided into two groups, one group was laser shock treated, and the other group was not laser shock treated as a control group. The creep aging test was completed through three stages of loading, creep aging forming and unloading. The sample was subjected to hardness test, microstructure analysis and rebound test.
[0100] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0101] The above describes specific embodiments of this specification, and other embodiments are within the scope of the appended claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily have to be performed in the specific order or continuous order shown to achieve the desired results. The various embodiments in this specification are described in a progressive manner, and the same and similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0102] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0103] The above is only an embodiment of this specification and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for forming an aluminum-lithium alloy component by laser shock and ultrasonic vibration assisted creep aging forming, characterized in that: include: performing a solid solution treatment on the first aluminum-lithium alloy component to obtain a second aluminum-lithium alloy component; Performing laser shock treatment on the entire upper surface or lower surface of the second aluminum-lithium alloy component to obtain a third aluminum-lithium alloy component; Performing deformation treatment on the third aluminum-lithium alloy component to obtain a fourth aluminum-lithium alloy component; When the fourth aluminum-lithium alloy component reaches a preset deformation, performing ultrasonic vibration assisted creep aging heat treatment on the fourth aluminum-lithium alloy component; The fourth aluminum-lithium alloy component after heat treatment is cooled to room temperature to obtain a fifth aluminum-lithium alloy component, and the creep aging forming of the fifth aluminum-lithium alloy component is analyzed.
2. The method according to claim 1, characterized in that Before the entire upper surface or lower surface of the second aluminum-lithium alloy component is subjected to laser shock treatment, the method further comprises: The working parameters of the laser shock treatment are set according to the thickness of the aluminum-lithium alloy component, and the working parameters at least include shock energy, spot diameter, spot overlap rate, pulse width, and number of shocks.
3. The method according to claim 1, characterized in that Before the deformation treatment is performed on the third aluminum-lithium alloy component, the method further comprises: The third aluminum-lithium alloy component is placed in a creep aging device, wherein the creep aging device at least includes a male mold and a female mold matching the male mold; the upper surface after laser shock treatment or the lower surface after laser shock treatment is in contact with the surface of the male mold, and the other surface is in contact with the surface of the female mold; The creep aging device is loaded by using a press machine so as to cause the third aluminum-lithium alloy component located in the creep aging device to deform.
4. The method according to claim 1, characterized in that The step of performing ultrasonic vibration assisted creep aging heat treatment on the fourth aluminum-lithium alloy component specifically includes: placing the fourth aluminum-lithium alloy component in a high-temperature furnace and heating it to a preset temperature; The fourth aluminum-lithium alloy component in the creep aging device in a heat-insulating state is subjected to ultrasonic vibration treatment at a preset vibration frequency.
5. The method according to claim 4, characterized in that If the preset vibration frequency is the natural frequency of the creep aging device, before performing ultrasonic vibration treatment on the fourth aluminum-lithium alloy component in the creep aging device according to the preset vibration frequency, the method further includes: The mechanical performance parameters of the creep aging device are obtained and combined with a finite element simulation algorithm to determine the natural frequency of the creep aging device.
6. The method according to claim 3, characterized in that The method further comprises: Determining a first curvature radius of the fourth aluminum-lithium alloy component according to the curvature radius of the profile surface of the concave die; Using preset reverse engineering software to perform solid modeling to determine a second radius of curvature of the fifth aluminum-lithium alloy component; The springback amount and springback rate of the creep aging forming of the aluminum-lithium alloy are determined according to the first radius of curvature and the second radius of curvature.
7. The method according to claim 1, characterized in that After cooling the creep aging device after the heat treatment to room temperature to obtain the fifth aluminum-lithium alloy component, the method further comprises: The upper and lower surfaces of the fifth aluminum-lithium alloy component are observed and hardness tested, and the microstructure and hardness changes of the fifth aluminum-lithium alloy component are analyzed.
Citation Information
Cited By
Ultrasonic impact strengthening equipment and method based on reverse elastic preloading
CN122081639A
Ultrasonic-assisted heat treatment process for rapid strengthening of aluminum-lithium alloys
NL2041014A